Dry electrode binder and preparation method thereof, dry electrode sheet

By using polyethylene glycol-fumarate as a dry electrode binder and grafting sulfonating reagent on its main chain, the problem of limited application of PTFE in the field of lithium batteries is solved. A more efficient and low-cost electrode manufacturing process is achieved, and the overall performance and processability of the electrode are improved.

CN119193077BActive Publication Date: 2025-02-25SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411722485.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing dry electrode adhesive polytetrafluoroethylene (PTFE) has problems such as high processing difficulty, insufficient flexibility, limited bonding performance and poor conductivity, which limits its wide application in the field of lithium batteries.

Method used

The binder is prepared by dissolution, esterification, neutralization, evaporation and concentration and purification steps, and is mainly used to prepare the binder. Graft sulfonic acid chlorine or sulfonic anhydride on the chain to improve its bonding properties and conductivity.

Benefits of technology

PEG-Fumarate can achieve film formation under lower temperature and pressure conditions, reduce energy consumption and equipment requirements, significantly simplify production processes, improve the flexibility, bonding performance and conductivity of the electrodes, and extend the cycle of the battery. Lifespan and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The embodiment of the present invention discloses a dry electrode binder and a preparation method thereof, and a dry electrode pole piece, wherein the binder comprises polyethylene glycol fumarate. The present invention significantly saves production costs, improves manufacturing efficiency, and makes large-scale production more feasible; the present invention makes the electrode structure more stable, prolongs the cycle life of the battery, and is particularly suitable for applications with high requirements for mechanical strength and durability; the present invention improves the overall performance and reliability of the electrode, improves the conductivity and rate performance of the electrode, and makes it suitable for high-power applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a dry electrode binder and a preparation method thereof, and a dry electrode pole piece. Background Art

[0002] In the traditional wet electrode manufacturing process, organic solvents (such as NMP, N-methylpyrrolidone) are usually used to mix active materials, conductive agents and binders into slurry. The slurry is then evenly coated on the metal foil current collector, and then the electrode is prepared through drying, compaction and other steps. The wet process has the advantages of good film formation and uniform dispersion of active materials, and is widely used in the current production of lithium-ion batteries. However, the disadvantages of this process are also significant. The main reason is that the organic solvent NMP used is toxic and volatile, which not only pollutes the environment, but also increases the solvent recovery and processing costs of the process. In addition, the wet process has many steps, the drying step is time-consuming and energy-consuming, and the equipment maintenance cost is high. Therefore, with the increasing demand of the battery industry for environmentally friendly and low-cost production processes, the dry process has gradually entered the research field of view.

[0003] Dry electrodes use solid powder to directly mix active materials, conductive agents and binders (also known as adhesives, bonding agents, bonding agents, etc.) together, and then apply the mixture to the current collector (such as aluminum foil or copper foil) by pressing or other mechanical methods.

[0004] In the early exploration of dry electrode preparation, researchers tried to simplify the process and reduce environmental impact by reducing or completely eliminating the use of solvents. The core of dry electrode technology is to achieve the fiberization of the binder during the powder mixing process to form a self-supporting dry electrode film. At present, the dry process uses polytetrafluoroethylene (PTFE) as a binder. PTFE has excellent chemical stability and mechanical properties and is insoluble in organic solvents. By mixing PTFE powder with active materials and then applying high temperature and pressure, the PTFE binder is tightly combined to form an electrode film. In addition, another approach to the dry process is to use a hot melt adhesive. This technology mainly relies on the heated fluidity of thermoplastic materials. The active material and the binder are mixed when heated to form an electrode film, which is fixed after cooling. This method reduces the use of solvents, but has high requirements on the temperature resistance and chemical stability of the binder material.

[0005] Although polytetrafluoroethylene (PTFE) has excellent chemical stability and mechanical strength as a dry electrode binder, it has some significant disadvantages that limit its widespread application in the battery field. First, PTFE is difficult to process. Its melting point is about 327°C, and it needs to be processed under high temperature and high pressure, which makes the process complicated and energy-intensive, making it difficult to achieve low-cost and high-efficiency large-scale production. In addition, after forming an electrode film, PTFE is usually brittle, lacks flexibility, and lacks ductility, which makes the electrode prone to cracking or peeling when subjected to mechanical stress during charging and discharging, affecting the structural stability and cycle life of the battery. Secondly, PTFE has limited bonding properties. Although it can bond active materials together under high temperature and high pressure, it has weak adhesion to irregular or high-surface-area material surfaces, resulting in separation or particle shedding of active materials after multiple charge and discharge cycles, thereby affecting battery performance. In addition, PTFE itself is an electrical insulator and does not have electronic or ionic conductivity. When used, a large amount of conductive agents (such as carbon black or carbon nanotubes) need to be added to improve the conductivity of the electrode, which will increase the material cost and may affect the overall performance of the electrode. The processing equipment requirements are also high. Since PTFE needs to be processed under high temperature and high pressure conditions, the cost of related equipment is high, and the high friction coefficient of PTFE may cause increased equipment wear, further increasing equipment maintenance costs. In addition, the chemical inertness of PTFE makes it difficult to form stable chemical bonds with other materials, showing poor compatibility, which limits its synergistic effect with other binders or functional materials. In general, although PTFE performs well in high temperature and chemical corrosion resistance, its shortcomings such as processing complexity, insufficient flexibility, limited bonding performance and poor conductivity have greatly limited its application in the field of lithium batteries. Summary of the invention

[0006] The technical problem to be solved by the embodiments of the present invention is to provide a dry electrode binder and a preparation method thereof, and a dry electrode pole piece, so as to improve the overall performance and processability of the electrode material.

[0007] In order to solve the above technical problems, an embodiment of the present invention provides a dry electrode binder including polyethylene glycol-fumarate.

[0008] Furthermore, sulfonic acid chloride or sulfonic acid anhydride is grafted onto the main chain of polyethylene glycol-fumarate.

[0009] Accordingly, an embodiment of the present invention further provides a method for preparing a dry electrode binder, comprising:

[0010] Dissolution step: Take appropriate amounts of polyethylene glycol and fumaric acid, add reaction solvent to completely dissolve PEG and fumaric acid to form a uniform solution;

[0011] Esterification reaction steps: add an appropriate amount of catalyst to the solution and stir evenly;

[0012] Neutralization treatment step: after the reaction is completed, add an appropriate amount of dilute sodium hydroxide solution to the solution to neutralize the residual acid catalyst, and wash to remove the reaction by-products and residual acid to obtain a polyethylene glycol-fumarate solution;

[0013] Evaporation and concentration step: evaporating and concentrating the polyethylene glycol-fumarate solution to obtain a concentrated product;

[0014] Purification step: The concentrated product is recrystallized from a solvent and then vacuum dried to obtain pure polyethylene glycol-fumarate powder.

[0015] Furthermore, in the dissolving step, the molar ratio of polyethylene glycol to fumaric acid is 1:1 or 2:1.

[0016] Furthermore, in the esterification reaction step, p-toluenesulfonic acid is used as a catalyst, and the amount of p-toluenesulfonic acid used is 0.5-1% of the total mass of the reactants.

[0017] Furthermore, in the esterification reaction step, an appropriate amount of anhydrous sodium sulfate or anhydrous calcium chloride is added as a dehydrating agent to absorb the water generated by the esterification reaction to prevent the water from affecting the efficiency of the esterification reaction.

[0018] Furthermore, in the evaporation and concentration step, the reaction solvent was removed using a rotary evaporator at 40–50 °C.

[0019] Furthermore, the reaction solvent in the dissolving step is dichloromethane.

[0020] Furthermore, in the purification step, ethanol or a dichloromethane / ethanol mixed solvent is used for solvent recrystallization.

[0021] Correspondingly, an embodiment of the present invention further provides a dry electrode plate, which uses polyethylene glycol-fumarate as an adhesive.

[0022] The beneficial effects of the present invention are: the processing simplicity and low energy consumption of the present invention: polyethylene glycol-fumarate (PEG-Fumarate) can form a film under relatively low temperature and pressure conditions, while PTFE requires high temperature (about 327°C) and high pressure environment to be processed into an electrode film. This feature of PEG-Fumarate significantly simplifies the production process, reduces energy consumption and equipment requirements, thereby achieving a more efficient and low-cost electrode manufacturing process. The positive effect is that it significantly saves production costs, improves manufacturing efficiency, and makes large-scale production more feasible.

[0023] Flexibility and mechanical stability: The molecular structure of PEG-Fumarate provides better flexibility, which can adapt to the volume changes of the electrode during the charge and discharge process, reduce cracking and peeling of electrode materials. This is different from the rigidity and brittleness of PTFE. PEG-Fumarate is better able to cope with the mechanical stress caused by multiple cycles. The positive effect is that the electrode structure is more stable, which prolongs the cycle life of the battery, especially for applications with high requirements for mechanical strength and durability.

[0024] Enhanced bonding properties: PEG-Fumarate can form stronger adhesion to active materials through intermolecular polar interactions and adjustable functional groups, while PTFE has weaker bonding properties, especially on irregular or high surface area materials. The chemical activity and polarity of PEG-Fumarate are more conducive to stabilizing electrode materials. The positive effect is to reduce particle shedding and separation of active materials, thereby improving the overall performance and reliability of the electrode.

[0025] Easy to compound with conductive additives: PEG-Fumarate can disperse conductive fillers (such as carbon nanotubes, graphene or conductive carbon black) more evenly to form a continuous conductive network, thereby improving the conductivity of the electrode. PTFE, as an insulator, has poor conductivity itself and requires a large amount of conductive fillers, but its poor dispersion performance affects the overall electrode performance. The positive effect of this advantage of PEG-Fumarate is to improve the conductivity and rate performance of the electrode, making it suitable for high-power applications.

[0026] Environmental protection and safety: PEG-Fumarate does not involve harmful solvents (such as NMP) or complicated recycling processes, meeting higher environmental and safety standards. In contrast, high-temperature processing of PTFE may bring environmental and safety risks, especially during manufacturing and handling. The positive effect is a more environmentally friendly and safe production environment, which meets the requirements of sustainable development. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments may be combined with each other. The present invention will be further described in detail below in conjunction with specific embodiments.

[0028] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0029] The dry electrode binder of the embodiment of the present invention uses polyethylene glycol-fumarate. The dry electrode plate of the embodiment of the present invention uses polyethylene glycol-fumarate as a binder, that is, polyethylene glycol-fumarate (PEG-Fumarate) is used to replace polytetrafluoroethylene (PTFE) to prepare it.

[0030] The present invention uses polyethylene glycol-fumarate (PEG-Fumarate) instead of polytetrafluoroethylene (PTFE) as a dry electrode binder to solve some key problems, thereby improving the overall performance and processability of the electrode material.

[0031] First, PEG-Fumarate is relatively easy to process, and does not require high temperature and high pressure conditions like PTFE to form a film. This makes the production process simpler, reduces energy consumption, and significantly reduces production costs. PEG-Fumarate can be cross-linked and bonded at lower temperatures, which helps improve manufacturing efficiency and reduce equipment requirements. In addition, PEG-Fumarate is more flexible than PTFE and can better adapt to the volume changes of electrode materials during charging and discharging, thereby reducing cracking or delamination problems caused by mechanical stress. This feature helps to improve the structural stability and cycle life of the battery.

[0032] In terms of bonding performance, PEG-Fumarate can form strong adhesion with active materials, especially through chemical modification, which can further enhance its bonding performance. Compared with the weaker bonding of PTFE, this significantly reduces the separation or particle shedding of active materials that may occur after multiple cycles. In addition, PEG-Fumarate has certain polarity and chemical activity, and can improve its compatibility with active materials through functional group modification, providing a more reliable bonding effect and avoiding the compatibility problems caused by the chemical inertness of PTFE.

[0033] Although PEG-Fumarate also does not have electronic conductivity, it can be more easily compounded with conductive fillers (such as carbon nanotubes or graphene) to form a conductive network. Due to its good dispersibility and flexibility, it can more evenly distribute conductive materials and improve the overall conductivity of the electrode. This property makes up for the impact of PTFE on electrode conductivity when it is an insulator. In addition, the hydrophilicity and chemical adjustability of PEG-Fumarate can improve the overall dispersibility and processing performance of the material, solving the limitations of PTFE in chemical inertness.

[0034] In summary, using PEG-Fumarate instead of PTFE can solve problems such as high processing difficulty, insufficient flexibility, weak bonding performance, high equipment requirements and poor compatibility, thereby improving the production efficiency, cycle stability and overall electrochemical performance of dry electrodes.

[0035] As an embodiment, sulfonic acid chloride or sulfonic acid anhydride is grafted onto the main chain of polyethylene glycol-fumarate. The present invention chemically modifies polyethylene glycol-fumarate by grafting a sulfonating agent (sulfonic acid chloride or sulfonic acid anhydride) onto the main chain of PEG-Fumarate, thereby increasing the ionic conductivity of the polyethylene glycol-fumarate binder.

[0036] Characteristics and applications of the sulfonated PEG-Fumarate of the embodiments of the present invention:

[0037] Improved ion conductivity: The grafted sulfonic acid groups provide a proton conduction path, making the material have higher ion conductivity. For dry electrode binders, this can significantly improve the ion transport performance at the electrode interface and improve the overall battery performance.

[0038] Adhesion performance and structural stability: The modified PEG-Fumarate not only maintains its good adhesion performance, but also enhances its compatibility with active materials by adding polar groups, further improving the stability of the electrode.

[0039] The functional differences between the sulfonated PEG-Fumarate of the present invention and PTFE are as follows:

[0040] Processing temperature and energy consumption: PTFE requires high temperature and high pressure processing, while PEG-Fumarate can form a film at a lower temperature, reducing energy consumption and simplifying the process. This is a significant difference in processability between the two.

[0041] Bonding mechanism: PTFE mainly relies on physical action for bonding, and has limited adhesion to the surface of active materials, especially on hydrophobic materials. However, PEG-Fumarate can introduce polar functional groups through chemical modification, forming stronger chemical or physical adhesion with active materials and improving bonding performance.

[0042] Flexibility and mechanical response: The high rigidity of PTFE causes the electrode to be prone to cracks or structural damage during the cycle, while PEG-Fumarate has better flexibility and can better buffer mechanical stress and extend the service life of the electrode.

[0043] Conductivity regulation: PTFE itself is an insulator with poor conductivity, while PEG-Fumarate can be more effectively compounded with conductive materials to form a more uniform conductive network and improve the overall conductive performance.

[0044] The preparation method of the dry electrode binder of the embodiment of the present invention comprises:

[0045] Dissolution step: Take appropriate amounts of polyethylene glycol and fumaric acid, add reaction solvent to completely dissolve PEG and fumaric acid to form a uniform solution;

[0046] Esterification reaction steps: add an appropriate amount of catalyst to the solution and stir evenly;

[0047] Neutralization treatment step: after the reaction is completed, add an appropriate amount of dilute sodium hydroxide solution to the solution to neutralize the residual acid catalyst, and wash to remove the reaction by-products and residual acid to obtain a polyethylene glycol-fumarate solution;

[0048] Evaporation and concentration step: evaporating and concentrating the polyethylene glycol-fumarate solution to obtain a concentrated product;

[0049] Purification step: The concentrated product is recrystallized from a solvent and then vacuum dried to obtain pure polyethylene glycol-fumarate powder.

[0050] Raw materials preparation:

[0051] Polyethylene glycol (PEG): Choose PEG with different molecular weights according to your needs, generally 200–6000.

[0052] Fumaric acid: chemical reagent.

[0053] Solvents: dichloromethane (DCM), toluene, etc., used for reaction and purification.

[0054] Catalyst: p-toluenesulfonic acid (PTSA) or sulfonic acid type catalyst.

[0055] Dehydrating agent: anhydrous sodium sulfate or anhydrous calcium chloride, used to remove water.

[0056] Neutralizer: Sodium hydroxide solution, acid catalyzed reaction.

[0057] The preparation method mainly comprises the following steps:

[0058] 1. Raw material preparation steps

[0059] PEG: Take PEG of the required molecular weight, weigh it and dry it in a vacuum oven at 60°C for several hours to remove adsorbed moisture.

[0060] Fumaric Acid: Fumaric acid is dried to ensure it is pure and free of moisture by drying it in a vacuum desiccator for several hours.

[0061] 2. Dissolution Step

[0062] Appropriate amounts of PEG and fumaric acid were added to the reaction flask in a molar ratio (1:1 or 2:1).

[0063] Add solvent (such as dichloromethane) and place the reaction flask in a water or oil bath and heat to 45–70°C to completely dissolve the PEG and fumaric acid to form a homogeneous solution.

[0064] 3. Esterification reaction steps

[0065] Catalyst addition: Add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst and stir evenly. The amount of catalyst used is generally 0.5-1% of the total mass of the reactants.

[0066] Reaction conditions: Maintain the temperature at 45–70°C and stir continuously for 4–6 hours. A small amount of water will be produced during the esterification reaction.

[0067] Dehydration: Add an appropriate amount of anhydrous sodium sulfate or anhydrous calcium chloride as a dehydrating agent to absorb the water generated by the reaction to prevent the water from affecting the efficiency of the esterification reaction.

[0068] Reaction monitoring: Monitor the progress of the reaction by thin layer chromatography (TLC) or infrared spectroscopy (IR) and observe the changes in the absorption peak of the ester group of fumaric acid to determine the completion of the reaction.

[0069] 4. Neutralization steps

[0070] Neutralization of acidic catalyst: After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acidic catalyst in the system.

[0071] Washing: Wash the product in the reaction system with distilled water several times to remove reaction by-products and residual acid.

[0072] 5. Evaporation and concentration steps

[0073] The reaction solvent (e.g., dichloromethane) is removed using a rotary evaporator at 40–50°C to obtain a semi-solid crude product. To remove the residual solvent, the product is dried in a vacuum oven at low temperature to ensure that no thermal decomposition occurs.

[0074] 6. Purification Steps

[0075] The concentrated product is recrystallized from a solvent (e.g., ethanol or a dichloromethane / ethanol mixed solvent) to obtain pure PEG-Fumarate. The crystalline product is separated by filtration and dried in a vacuum drying oven to obtain pure polyethylene glycol-fumarate powder.

[0076] The esterification reaction of PEG and fumaric acid to form polyethylene glycol-fumarate mainly involves the following reaction formula:

[0077] 1. PEG and fumaric acid esterification:

[0078]

[0079] 2. Dehydration reaction (the generated water is absorbed by anhydrous sodium sulfate):

[0080] H2O+Na2SO4→Na2SO4·H2O

[0081] 3. Acid catalyst neutralization:

[0082] PTSA+NaOH→NaPTSA+ H2O

[0083] Purified polyethylene glycol-fumarate (PEG-Fumarate) products can be obtained through these reactions. Purified polyethylene glycol-fumarate is chemically modified by grafting a sulfonating agent (sulfonic acid chloride or sulfonic acid anhydride) onto the main chain of PEG-Fumarate.

[0084] Raw materials preparation:

[0085] PEG-Fumarate: Select PEG-Fumarate of appropriate molecular weight.

[0086] Sulfonation reagent: Sulfonic acid chloride (Cl-SO3H) or sulfonic anhydride (such as sulfonated methyl anhydride) is selected as the reagent for the sulfonation reaction.

[0087] Catalyst and solvent: Use an appropriate amount of organic base (such as pyridine) as an acid scavenger and select a suitable anhydrous solvent (such as dichloromethane or dimethyl sulfoxide) to carry out the reaction.

[0088] 1. Dissolving and cooling:

[0089] Dissolve PEG-Fumarate in an appropriate amount of anhydrous dichloromethane (DCM) and cool to 0°C in an ice bath. Control the temperature of the sulfonation reaction to prevent side reactions.

[0090] 2. Addition of sulfonating agent:

[0091] Slowly add sulfonic acid chloride dropwise to the cooled PEG-Fumarate solution while stirring continuously to ensure a uniform reaction. During this process, the sulfonic acid amine reacts with the fumarate group of PEG-Fumarate to form a sulfonic acid grafted product.

[0092] Chemical reaction formula (taking sulfonic acid chloride as an example):

[0093] PEG-Fumarate+Cl-SO3H→PEG-Fumarate-SO3H+HCl

[0094] In this reaction, sulfonic acid chloride introduces -SO3H groups into the main chain of PEG-Fumarate, while generating HCl as a byproduct.

[0095] 3. The role of acid capture agent:

[0096] In order to neutralize the HCl generated in the reaction, an appropriate amount of pyridine is added as an acid scavenger to form a pyridinium salt to prevent HCl from having an adverse effect on the structure of the polymer. The acid scavenger can also help improve the yield and stability of the reaction.

[0097] Neutralization reaction formula:

[0098] HCl+C5H5N→C5H5NHCl

[0099] Among them, C5H5N represents pyridine, and C5H5NHCl is the generated pyridinium salt.

[0100] 4. End of reaction and product purification:

[0101] After the reaction is completed, the mixture is heated to room temperature and stirred for several hours to ensure that the sulfonation reaction is fully carried out. Subsequently, the product is washed with anhydrous ether to remove unreacted sulfonation reagent and by-products.

[0102] The solvent was removed by rotary evaporation to obtain sulfonic acid grafted PEG-Fumarate powder. Example 1

[0103] Weigh and dry PEG with a molecular weight of 200 and dry it in a vacuum oven at 60°C for 3 hours to remove adsorbed moisture. Dry fumaric acid in a vacuum dryer for 1 hour. Add appropriate amounts of PEG and fumaric acid in a molar ratio (1:1) to a reaction flask. Add dichloromethane and place the reaction flask in a water bath or oil bath and heat to 60°C to completely dissolve PEG and fumaric acid to form a uniform solution.

[0104] Add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst and stir evenly. The amount of catalyst used is generally 0.5% of the total mass of the reactants. Keep the temperature at 60°C and continue stirring for 4 hours. Add an appropriate amount of anhydrous sodium sulfate as a dehydrating agent to absorb the moisture generated by the reaction to prevent moisture from affecting the efficiency of the esterification reaction. Monitor the progress of the reaction by thin layer chromatography (TLC) and observe the changes in the absorption peak of the ester group of fumaric acid to determine that the reaction is complete.

[0105] After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acid catalyst in the system. The product in the reaction system is washed with distilled water several times to remove the reaction by-products and residual acid. The reaction solvent (dichloromethane) is removed at 40°C using a rotary evaporator to obtain a semi-solid crude product. To remove the residual solvent, the product is dried at low temperature in a vacuum oven to ensure that thermal decomposition is not caused.

[0106] The concentrated product was recrystallized from a solvent (using a dichloromethane / ethanol mixed solvent) to obtain pure PEG-Fumarate. The crystalline product was separated by filtration and dried in a vacuum drying oven to obtain pure polyethylene glycol-fumarate powder.

[0107] Purified polyethylene glycol-fumarate was chemically modified by grafting the sulfonating agent (sulfonic acid chloride) onto the main chain of PEG-Fumarate.

[0108] Select sulfonic acid chloride (Cl-SO3H) as the reagent for the sulfonation reaction. Use an appropriate amount of organic base (such as pyridine) as an acid capture agent and select a suitable anhydrous solvent (such as dichloromethane) to carry out the reaction. Dissolve PEG-Fumarate in an appropriate amount of anhydrous dichloromethane (DCM) and cool it to 0°C in an ice bath. Control the temperature of the sulfonation reaction to prevent side reactions. Slowly add sulfonic acid chloride to the cooled PEG-Fumarate solution while stirring continuously to ensure a uniform reaction.

[0109] After the reaction is complete, the mixture is heated to room temperature and stirred for several hours to ensure that the sulfonation reaction is fully carried out. Subsequently, the product is washed with anhydrous ether to remove unreacted sulfonation reagent and by-products. The solvent is removed by rotary evaporation to obtain sulfonic acid grafted PEG-Fumarate powder.

[0110] A lithium-ion battery positive electrode dry electrode with sulfonic acid grafted PEG-Fumarate powder as a binder was prepared. Lithium iron phosphate (LiFePO4) was used as the active material, conductive carbon black as the conductive agent, and aluminum foil as the current collector.

[0111] The implementation steps are as follows: 90 wt% lithium iron phosphate, 5 wt% sulfonic acid grafted PEG-Fumarate powder and 5 wt% conductive carbon black are weighed and mixed thoroughly in a high-speed mixer to ensure that the binder and conductive carbon black are evenly dispersed between the active material particles. Then, the mixture is pressed into an electrode film with a uniform thickness of 100 microns, and the volume resistance test and bonding strength test are performed. Example 2

[0112] Weigh PEG with a molecular weight of 1000 and dry it in a vacuum oven at 70°C for 2 hours to remove all adsorbed moisture. Treat fumaric acid in a vacuum desiccator at 60°C for 1 hour. Add PEG and fumaric acid to the reaction flask in a molar ratio of 1:1, use dimethyl sulfoxide (DMSO) as a solvent, and place the flask in a water bath and heat it to 50°C until it is completely dissolved to form a uniform solution. Add 0.3% p-toluenesulfonic acid (PTSA) as a catalyst, stir evenly, and keep the reaction temperature at 50°C, and continue stirring for 6 hours. Add anhydrous calcium chloride as a dehydrating agent to remove the water generated in the reaction. After confirming the completion of the reaction by thin layer chromatography (TLC), add dilute sodium hydroxide solution to neutralize the residual acid catalyst in the system, and wash the reaction product with distilled water several times. Remove the solvent by rotary evaporator at 45°C to obtain a crude product, and dry it at low temperature in a vacuum oven at 40°C to remove the residual solvent. The dried crude product was recrystallized and a mixed solvent of ethanol and dichloromethane was used to obtain pure PEG-Fumarate powder. Sulfonic anhydride was used as the sulfonating agent. The temperature was controlled in an ice bath through the sulfonating reaction. PEG-Fumarate and sulfonic anhydride were reacted in the presence of pyridine. After the reaction was completed, it was washed with ether and the solvent was removed by rotary evaporation to obtain sulfonic acid grafted PEG-Fumarate powder. 90 wt% lithium iron phosphate, 5 wt% sulfonic acid grafted PEG-Fumarate and 5 wt% conductive carbon black were mixed, fully mixed in a high-speed mixer, and pressed into an electrode film with a thickness of 100 microns for volume resistance and bonding strength tests. Example 3

[0113] Weigh PEG with a molecular weight of 3000 and dry it in a vacuum oven at 80°C for 1.5 hours. Add the dried PEG and fumaric acid to the reaction flask in a 1:1 molar ratio, add dichloroethane as a solvent, and heat to 65°C in an oil bath and stir until dissolved. Use 0.6% PTSA as a catalyst, stir and maintain the reaction temperature at 65°C for 1.5 hours, then add anhydrous magnesium sulfate as a dehydrating agent to remove the water produced by the reaction. Monitor the reaction by TLC, neutralize with dilute sodium hydroxide after the reaction is completed, and wash with distilled water. Remove the solvent by rotary evaporation, dry the product in a vacuum oven and recrystallize to obtain high-purity PEG-Fumarate. Use sulfonic acid chloride as a sulfonating agent, and react in the presence of anhydrous ethanol. Control the temperature under ice bath conditions. After the reaction, wash with anhydrous ether and remove the solvent to obtain PEG-Fumarate powder grafted with sulfonic acid groups. 90 wt% lithium iron phosphate, 5 wt% sulfonic acid grafted PEG-Fumarate and 5 wt% conductive carbon black were weighed, mixed evenly and pressed into an electrode film with a thickness of 100 μm, and then volume resistance test and bonding strength test were carried out. Example 4

[0114] PEG with a molecular weight of 5000 was weighed and dried in a vacuum oven at 60°C for 2 hours to remove moisture. Fumaric acid was dried in a vacuum dryer at 80°C for 1.5 hours and then added to the reaction flask with PEG at a molar ratio of 2:1. Toluene was used as a solvent and heated to 70°C in an oil bath until dissolved. 0.4% PTSA was added as a catalyst and stirred for 2 hours. After the reaction, anhydrous calcium chloride was added to absorb moisture, and the product was washed with water after neutralization with dilute sodium hydroxide. The toluene solvent was removed by rotary evaporation and dried in a vacuum oven, followed by recrystallization to obtain pure PEG-Fumarate powder. Sulfonic acid chloride was used for sulfonation reaction in the presence of pyridine, and sulfonic acid chloride was slowly added under ice bath conditions. After the reaction, it was washed with ether, by-products were removed and dried to obtain PEG-Fumarate powder grafted with sulfonic acid groups. 90 wt% lithium iron phosphate, 5 wt% modified PEG-Fumarate and 5 wt% conductive carbon black were mixed and pressed into an electrode film with a thickness of 100 microns, and volume resistance test and bonding strength test were carried out.

[0115] Comparative Example

[0116] Weigh PEG and fumaric acid with a molecular weight of 200, add them to the reaction flask in a 1:1 molar ratio, use dichloromethane as the solvent, and heat in a 60°C water bath until completely dissolved. Add 0.5% PTSA as a catalyst, stir the reaction for 4 hours, add anhydrous sodium sulfate to remove moisture, neutralize with dilute sodium hydroxide and wash with water several times. Remove the solvent by rotary evaporation to obtain PEG-Fumarate powder that has not been sulfonated. Mix 90 wt% lithium iron phosphate, 5 wt% unmodified PEG-Fumarate and 5 wt% conductive carbon black and press into an electrode film with a thickness of 100 microns. Perform volume resistance test and bonding strength test.

[0117] The volume resistance test results are shown in Table 1.

[0118]

[0119] The bonding strength test results are shown in Table 2.

[0120]

[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A dry electrode binder, characterized in that: The invention comprises polyethylene glycol-fumarate, wherein sulfonic acid chloride or sulfonic acid anhydride is grafted on the main chain of the polyethylene glycol-fumarate, and the polyethylene glycol-fumarate is an esterification product obtained by reacting polyethylene glycol and fumaric acid, and further reacts with sulfonic acid chloride or sulfonic acid anhydride to generate polyethylene glycol-fumarate with sulfonic acid chloride or sulfonic acid anhydride grafted on the main chain; the molar ratio of the polyethylene glycol and fumaric acid is 1:1 or 2:1, the reaction temperature of the polyethylene glycol and fumaric acid is 45-70°C, and the reaction time of the polyethylene glycol and fumaric acid is 4-6 hours.

2. A method for preparing a dry electrode binder, characterized in that: include: Dissolution step: taking appropriate amounts of polyethylene glycol and fumaric acid, adding a reaction solvent to completely dissolve the PEG and fumaric acid to form a uniform solution; the molar ratio of the polyethylene glycol to the fumaric acid is 1:1 or 2:1; Esterification reaction steps: add an appropriate amount of catalyst to the solution and stir evenly; Neutralization treatment step: after the reaction is completed, add an appropriate amount of dilute sodium hydroxide solution to the solution to neutralize the residual acid catalyst, and wash to remove the reaction by-products and residual acid to obtain a polyethylene glycol-fumarate solution; Evaporation and concentration step: evaporating and concentrating the polyethylene glycol-fumarate solution to obtain a concentrated product; Purification step: the concentrated product is subjected to solvent recrystallization and then vacuum dried to obtain pure polyethylene glycol-fumarate powder; the polyethylene glycol-fumarate powder is dissolved in an appropriate amount of anhydrous dichloromethane to obtain a polyethylene glycol-fumarate solution, which is placed in an ice bath and cooled to 0°C; sulfonic acid chloride or sulfonic acid anhydride is slowly added dropwise to the cooled polyethylene glycol-fumarate solution while continuously stirring to ensure uniform reaction; an appropriate amount of pyridine is added as an acid scavenger to neutralize HCl generated in the reaction; after the reaction is completed, the polyethylene glycol-fumarate powder grafted with sulfonic acid chloride or sulfonic acid anhydride is purified; In the esterification step, p-toluenesulfonic acid is used as a catalyst, the amount of p-toluenesulfonic acid used is 0.5-1% of the total mass of the reactants, the reaction temperature is 45-70° C., and the stirring reaction time is 4-6 hours.

3. The method for preparing a dry electrode binder according to claim 2, characterized in that: In the esterification reaction step, an appropriate amount of anhydrous sodium sulfate or anhydrous calcium chloride is also added as a dehydrating agent to absorb the water generated by the esterification reaction to prevent the water from affecting the efficiency of the esterification reaction.

4. The method for preparing a dry electrode binder according to claim 2, characterized in that: During the evaporation and concentration steps, the reaction solvent was removed using a rotary evaporator at 40–50°C.

5. The method for preparing a dry electrode binder according to claim 2, characterized in that: The reaction solvent in the dissolving step was dichloromethane.

6. The method for preparing a dry electrode binder according to claim 2, characterized in that: In the purification step, ethanol or a dichloromethane / ethanol mixed solvent is used for solvent recrystallization.

7. A dry electrode plate, characterized in that: The polyethylene glycol-fumarate prepared by the method for preparing a dry electrode binder as described in any one of claims 2 to 6 is used as the binder.

Citation Information

Patent Citations

  • Electrolyte for driving ultrahigh voltage large-sized aluminium electrolytic capacitor and solute thereof

    CN101866752A